Building Leadership Storytelling Skills: A Collaboration Between Management and Theater Students. (June 2021) - Clark, Ryan M.; Kayes, Anna B.
Storytelling is an important skill in management education for leaders. However, even though students learn about storytelling, they do not often practice it. When students do practice storytelling, they frequently prepare speeches that they deliver in front of a class. Interacting with theater students can help management students convey a message in conversational format, which is more representative of the skill in practice. We present an experiential exercise involving collaboration between management and theater students that simulates a career networking event; the format of interactive drama offers a structured process for student engagement and leadership storytelling skill development.